CASE OF MULTIPATHOGEN-INDUCED MORTALITY IN AN OPEN-HOUSE BROILER FARM IN DEMULIH VILLAGE, BANGLI - Fiorell, Chrissyl; Widyasanti, Ni Wayan Helpina; Berata, I Ketut; Putra, I Putu Cahyadi; Nindhia, Tjokorda Sari (Buletin Veteriner Udayana, 2026)
The health and performance of commercial chicken are greatly influenced by poultry house environmental management. The application of open house system with poor management may act as a predisposing factor for multipathogen colonization in poultry. This condition can lead to multiple diseases due to concurrent infections involving fungal, bacterial, and protozoal agents. This study reports a case of multipathogen-related mortality in 29-day-old broiler chicken from an open house farm in Demulih Village, Bangli Regency, Bali. Diagnostic methods include anamnesis, physical examination, epidemiological data collection, gross pathology, histopathology, bacteriology, mycology, and parasitology. Gross pathological examination revealed yellowish-white nodules in the body cavity, lungs, and kidneys; surface damage of the liver and kidneys; and hemorrhage in the cecum. Histopathology showed septate hyphae and conidiophores in the lungs as well as schizonts in the cecum, indicating fungal and protozoal infection. Mycological examination using Sabouraud Dextrose Agar and subsequent macroscopic and microscopic identification confirmed the presence of Aspergillus flavus, Aspergillus fumigatus, and Mucor spp. Bacteriological examination identified colonies of Staphylococcus sp., Acinetobacter sp., and Klebsiella sp. Parasitological analysis of fecal samples revealed Eimeria spp. oocysts at a concentration of 34,450 oocysts/gram, classified as moderate infection. The case was diagnosed as multiple disease conditions caused by concurrent multipathogen infections of fungal, bacterial, and protozoal origin. Improvements in housing management, sanitation, feed storage, strict biosecurity, and housing system considerations are required to minimize the introduction of disease-causing pathogens.